Clinical presentation and outcomes of neonatal cholestasis: Experience from a tertiary care hospital - Haque, Emdadul; Kamal, MA (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Neonatal cholestasis is a disorder that develops in the first few months of life and is characterised by an increase in direct (conjugated) bilirubin and jaundice due to defective bile synthesis or excretion. Objective: To observe the clinical manifestation and outcome of neonatal cholestasis. Methods: This was a hospital‑based cross‑sectional study carried out among 50 children attending the Department of Pediatrics, Bangladesh Shishu Hospital & Institute (BSH&I), between January 2023 and December 2023. Cholestasis was considered to be conjugated bilirubin levels above 1 mg/dL when serum total bilirubin levels were below 5 mg/dL, or conjugated bilirubin was more than 20% of total when total bilirubin levels were above 5 mg/dL. Children with Jaundice due to other reasons than cholestasis were excluded from the study Results: Among the neonatal cholestasis cases majority (72%) were intrahepatic and 28% were extrahepatic cholestasis. Regarding etiology 13(26%) were idiopathic neonatal hepatitis, 12(24%) biliary atresia, 10(20%) were infection. Mean age of onset for extrahepatic cholestasis was 6.7±1.4 days, while for intrahepatic cholestasis it was 8.2±2.8 days. Mean age of admission for extrahepatic cholestasis was 78.9±21.8 days, while for intrahepatic cholestasis it was 75.4±16.9 days (p>0.05). Male 42.9% had extrahepatic cholestasis, whereas 21 (58.3%) had intrahepatic cholestasis (p>0.05). Twelve cases (85.7%) of persistent pale stool were found in extra-hepatic cholestasis, while eleven cases (30.6%) were detected in intra-hepatic cholestasis, which was substantially higher in terms of clinical presentation (p<0.05). Significantly higher improvement were found in intra hepatic cholestasis then Extra hepatic cholestasis [24(66.7%) vs 1(7.1%), p<0.01). Regarding mortality 7(50%) cases died in extra hepatic choleasis and 7(19.4%) died in Intra hepatic cholestasis (p<0.001). Conclusion: Common etiological factors of neonatal cholestasis include idiopathic newborn hepatitis, biliary atresia, infection, metabolic abnormalities, and hereditary cholestatic diseases. Extra-hepatic cholestasis was associated with persistent pale stool. Treatment seeking in tertiary care hospital was delayed. Intrahepatic cholestasis showed significantly better results than extrahepatic cholestasis. J Shaheed Suhrawardy Med Coll 2024; 16(1): 14-18